The Impact of Adiwiyata Program on Environmental Caring Character - Caddafie, Syahrizal Umar; Martuti, Nana Kariada Tri; Rudyatmi, Ely (FMIPA UNNES, 2017)
This study attempted to describe the impact of Adiwiyata on the environmental caring character of the citizen of State Senior High School 14 of Semarang. This research belonged to descriptivequalitative research. The respondents of the study were determined purposively with the criteria of the school citizen who were active in Adiwiyata activities. The data sources included principals, teachers, students and employees. The methods of data collection used interview, observation and documentation. The results showed that State Senior High School 14 of Semarang implemented environmental education (Indonesian: Pendidikan Lingkungan Hidup) (PLH) learning and environmental activities. The PLH learning process was conducted by discussion methods, practicum, direct observation, demonstration, and role play. The learning materials were developed by raising environmental issues. The assessment of learning outcomes included vegetable growing project, making recycled handicrafts, work method and presentation. The environmental activities conducted by students included daily cleaning, clean Friday, environmental extracurricular, environmental action. 3R waste management (reduce, reuse and recycle), electricity and water savings. This study concluded that Adiwiyata impacted on the environmental caring character building of the State Senior High School 14 of Semarang citizen including: the habituation of keeping the classroom and school environment cleanlines, saving electricity and water, managing the school waste and preserving the biodiversity.